Mengintegrasikan Sistem Teknologi dalam Manajemen Sarana dan Prasarana untuk Pendidikan yang lebih Modern - Valentin Dyah Fransisca (Universitas Negeri Malang, 2023)
Abstract: The use of technology in the management of educational facilities and infrastructure can provide a more modern, efficient, and productive learning experience. The integration of technology in the management of educational facilities and infrastructure can increase efficiency, effectiveness, and accuracy in the management of assets and resources in educational institutions. Therefore, the role of managers and stakeholders determines the success of education delivery, because they have facilitators, especially in providing facilities and infrastructure. This study aims to discuss how to integrate technology systems in the management of educational facilities and infrastructure to improve the quality of more modern education. In the digital era, information and communication technology is very important in increasing efficiency, effectiveness, and accuracy in managing resources in educational institutions. This article also discusses various technologies that can be integrated in the management of educational facilities and infrastructure, their benefits, and how to implement them. The use of technology can help in security management, maintenance, and monitoring the condition of educational facilities and infrastructure. It is hoped that this article can provide insight and inspiration for parties involved in the management of educational facilities and infrastructure to continue to innovate and improve the quality of education in Indonesia.Keywords: Facilities and Infrastructure Management, Monitoring, Technology, Innovation, EfficientAbstrak: Penggunaan teknologi dalam manajemen sarana dan prasarana pendidikan dapat memberikan pengalaman belajar yang lebih modern, efisien, dan produktif. Integrasi teknologi dalam manajemen sarana dan prasarana pendidikan dapat meningkatkan efisiensi, efektivitas, dan akurasi dalam pengelolaan aset dan sumber daya di lembaga pendidikan. Oleh karena itu peran manajer dan stakeholder menentukan keberhasilan penyelenggaraan pendidikan, sebab mereka ada fasilitator terutama dalam menyediakan sarana dan prasarana. Penelitian ini bertujuan untuk membahas tentang bagaimana mengintegrasikan sistem teknologi dalam manajemen sarana dan prasarana pendidikan untuk meningkatkan kualitas pendidikan yang lebih modern. Dalam era digital, teknologi informasi dan komunikasi menjadi hal yang sangat penting dalam meningkatkan efisiensi, efektivitas,dan akurasi dalam pengelolaan sumber daya di lembaga pendidikan. Artikel ini juga membahas berbagai teknologi yang dapat diintegrasikan dalam manajemen sarana dan prasarana pendidikan, manfaatnya, serta cara implementasinya. Penggunaan teknologi dapat membantu dalam manajemen keamanan, pemeliharaan, dan monitoring kondisi sarana dan prasarana pendidikan. Diharapkan artikel ini dapat memberikan wawasan dan inspirasi bagi pihak-pihak yang terlibat dalam manajemen sarana dan prasarana pendidikan untuk terus berinovasi dan meningkatkan kualitas pendidikan di Indonesia.Kata kunci: Manajemen Sarana dan Prasarana, Monitoring, Teknologi, Berinovasi, Efisien